Corrosion protection of the AA2198‐T8 alloy by environmentally friendly organic‐inorganic sol‐gel coating based on bis‐1, 2‐(triethoxysilyl) ethane. (25th November 2020) - Klumpp, Rafael Emil; Donatus, Uyime; da Silva, Rejane Maria Pereira; Antunes, Renato Altobelli; Machado, Caruline de Souza Carvalho; Milagre, Mariana Xavier; de Sousa Araujo, João V.; de Viveiros, Bárbara Victoria Gonçalves; Costa, Isolda
Abstract : In this work, a surface coating composed of organic‐inorganic hybrid sol‐gel based on bis‐1, 2‐(triethoxysilyl) (BTSE) ethane was applied on AA2198‐T8 samples, and its effect on corrosion resistance was investigated and compared with that of a chromate layer formed in a solution with hexavalent chromium ions. The corrosion resistance of BTSE coated samples was evaluated by immersion tests in sodium chloride solution (0.005 mol/L NaCl) and monitored by global electrochemical techniques such as electrochemical impedance spectroscopy (EIS) and local electrochemical techniques such as scanning vibrating electrode technique (SVET) and scanning electrochemical microscopy (SECM). The formed coating layers were characterized by X‐ray photoelectron spectroscopy (XPS). The results pointed out that the BTSE is an effective alternative coating for corrosion protection of new generation Al‐Cu‐Li alloys and could replace chromates obtained in toxic and carcinogenic CrVI containing solutions leading to improved corrosion protection.